Speaking their language – Development of a multilingual decision-support tool for communicating invasive species risks to decision makers and stakeholders. (January 2021) - Copp, Gordon H.; Vilizzi, Lorenzo; Wei, Hui; Li, Shan; Piria, Marina; Al-Faisal, Abbas J.; Almeida, David; Atique, Usman; Al-Wazzan, Zainab; Bakiu, Rigers; Bašić, Tea; Bui, Thuyet D.; et al.
Abstract: Environmental changes due to non-native species introductions and translocations are a global concern. Whilst understanding the causes of bioinvasions is important, there is need for decision-support tools that facilitate effective communication of the potential risks of invasive non-native species to stakeholders. Decision-support tools have been developed mostly in English language only, which increases linguistic uncertainty associated with risk assessments undertaken by assessors not of English mother tongue and who need to communicate outcomes to local stakeholders. To reduce language-based uncertainty, the 'ecology-of-language' paradigm was applied when developing the Aquatic Species Invasiveness Screening Kit (AS-ISK), a decision-support tool that offers 32 languages in which to carry out screenings and communicate outcomes to stakeholders. Topics discussed include uncertainty related to language-specific issues encountered during the AS-ISK translation and the potential benefits of a multilingual decision-support tool for reducing linguistic uncertainty and enhancing communication between scientists, environmental managers, and policy and decision makers.